Institutional investors, corporate ownership and corporate governance: Global perspectives - Stuart L. Gillan; Laura T. Starks (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
We examine the role of institutional investors in financial markets and in corporate governance. In many countries, institutional investors have become the predominant players in financial markets and their influence worldwide is growing, chiefly due to the privatization and development of pension fund systems. Moreover, foreign institutional investors are becoming a significant presence, bringing their trading habits and corporate governance preferences to international markets. In fact, we argue that the primary actors prompting change in many corporate governance systems are institutional investors, often foreign institutional investors. In other countries the role of institutional investors is limited. Instead, large blockholders, often in the form of individuals, family groups, other corporations, or lending institutions are the dominant players. We present the theoretical arguments for the involvement of investors in shareholder monitoring and a brief history of institutional ownership and activism in the United States and other countries. We also discuss studies of the efficacy of such activism. We then examine differences in ownership structures around the world and the implications of the interactions of these ownership structures for institutional investor involvement in corporate governance. Although there may be some convergence in corporate governance systems across countries, because of the endogenous nature of the interrelation among the factors of corporate governance the evolution will most likely vary across countries. We would expect, however, that over time institutional investors will increase the liquidity, volatility, and price informativeness of the financial markets in which participate. In turn, the increased information provided by institutional trading should result in better corporate governance structures, including more effective monitoring.
Keywords: D23; F23; G32; G34; 330; institutional investors; corporate ownership; corporate governance; Institutioneller Anleger; Finanzmarkt; Corporate Governance; Eigentümerstruktur; Welt